Multisensory, Nature-Inspired Recharge Rooms Yield Short-Term Reductions in Perceived Stress Among Frontline Healthcare Workers - Putrino, David; Ripp, Jonathan; Herrera, Joseph E.; Cortes, Mar; Kellner, Christopher; Rizk, Dahlia; Dams-O’Connor, Kristen (Frontiers in Psychology, 2020)
We are currently facing global healthcare crisis that has placed unprecedented stress on healthcare workers as a result of COVID-19. It is imperative that we develop novel tools to assist healthcare workers in dealing with the significant additional stress and trauma that has arisen as a result of the pandemic. Based in research on the effects of immersive environments on mood, a neuroscience research laboratory was rapidly repurposed using commercially available technologies and materials to create a nature-inspired relaxation space. Frontline healthcare workers were invited to book 15-minute experiences in the Recharge Room before, during or after their shifts, where they were exposed to the immersive, multisensory experience 496 Recharge Room users (out of a total of 562) completed a short survey about their experience during an unselected, consecutive 14-day period. Average self-reported stress levels prior to entering the Recharge Room were 4.58/6 (±1.1). After a single 15-minute experience in the Recharge Room, the average user-reported stress level was significantly reduced 1.85/6 (±1.2; p<0.001; paired t-test). Net Promoter score for the experience was 99.3%. Recharge Rooms such as those described here produce significant short-term reductions in perceived stress, and users find them highly enjoyable. These rooms may be of general utility in high-stress healthcare environments.